A blind spot in fMRI research: Overlooked tobacco smoking-related confounds - Merel Koster; Marieke van der Pluijm; Lieuwe de Haan; Guido van Wingen; Jentien Vermeulen (NeuroImage, 2025)
The confounding effects of smoking are often overlooked in functional magnetic resonance imaging (fMRI) research, potentially distorting results. By implementing clear guidelines and optimizing scan timing, studies can better account for tobacco's acute and withdrawal effects, improving precision and reproducibility of findings in studies involving smokers. Timing scans 1–2 h after the last cigarette in regular smokers (e.g. >10 cigarettes per day) may help minimize acute nicotine effects and early withdrawal symptoms. Further, we propose a standardized reporting framework that includes smoking frequency, nicotine dependence, and timing of the last cigarette relative to scanning.